Anion‐ and Solvent‐Induced Assembly and Reversible Structural Transformation of d10‐Metal Coordination Architectures Containing N‐(4‐(4‐Aminophenyloxy)phenyl)isonicotinamide. Issue 4 (16th December 2015) - Tzeng, Biing‐Chiau; Hung, Yu‐Ching; Lee, Gene‐Hsiang
Abstract: We set out studies on anion‐ and solvent‐induced assembly based on the ligand N ‐(4‐(4‐aminophenyloxy)phenyl)isonicotinamide (papoa), which is synthesized to show a bent and flexible backbone. Reactions of papoa with ZnX2 (X=Cl, Br, and I) gave the dinuclear macrocycles ([ZnX2 (papoa)]2 ; X=Cl (1 a ), Br (2 a ), I (3 )), the structure of which was determined by X‐ray diffraction. Notably, the less bulky Cl and Br compounds afforded the coordinated imine in acetone (i.e., [ZnX2 (papoi)]2, papoi= N ‐(4‐(4‐(propan‐2‐ylideneamino)phenoxy)phenyl)isonicotinamide; X=Cl (1 b ), Br (2 b )), whereas the iodine one only gave the coordinated amine compound3 under the same reaction condition. In fact, the coordinated imine can return to the amine analogue upon exposure to air or in DMSO, which has been monitored by 1 H NMR spectroscopy and powder X‐ray diffraction. Both the dinuclear [Zn(papoa)(NO3 )2 ]2 (4 a ) and the 1D [Zn(papoa)2 (NO3 )2 ] n (4 b ) were formed from the reaction of Zn(NO3 )2 and papoa in mixed solvents with acetone and acetonitrile, respectively. In addition, Cd(ClO4 )2 can react with papoa to give the 1D framework [Cd(papoa)2 (CH3 CN)2 ](ClO4 )2 n (5 a ) and the 2D framework [Cd(papoa)2 (ClO4 )2 ] n (5 b ), depending on the solvent used, that is, MeOH and CH3 CN, respectively. Importantly, the 1D framework with axially coordinated CH3 CN molecules and the 2D framework with axially coordinated ClO4 − ions can be interconverted by heating and grinding in the presence of CH3 CN, respectively. Such a reversible structural transformation process was proven by PXRD studies. Abstract : Switch it : The anion‐ and solvent‐induced assembly of Zn and Cd complexes based on the ligand N ‐(4‐(4‐aminophenyloxy)phenyl)isonicotinamide (papoa) has been investigated. It was shown that interconversion between different frameworks induced by heat or a change of the solvent occurs (see figure).